Historical archaeology in Central Europe - Mehler, Natascha 1970- (Society for Historical Archaeology, 2013)
25 articles that present archaeological analyses and interpretations on a variety of subjects from Germany, Austria, Switzerland, the Czech Republic, Slovenia, Slovakia, Hungary, and Poland. The articles collected for the purpose of this book offer a broad variety of topics and provide examples from urban, landscape, underwater, industrial, battlefield, aviation, and Ottoman archaeology, as well as material culture studies. Sites and case studies presented range chronologically from the 15th to the 20th century. Furthermore, this volume contains summaries of the status and theoretical foundations of historical archaeology in the various central European countries, and offers perspectives from each. The result is a volume that summarizes the state of historical archaeology in the region and lays a foundation for current and future generations of central European archaeologists to build upon
Includes bibliographical references
Keywords: Geschichte 1400-2000; Archäologie; Funde; Geschichte; Archaeology -- Europe, Central -- History; Sachkultur; Europe, Central -- Antiquities; Mitteleuropa; Aufsatzsammlung